2018
DOI: 10.2174/1872211311666171129121128
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone a Potential Therapeutic Molecule from the Plant Nigella sativa: Role of Colloidal Carriers in its Effective Delivery

Abstract: The findings of this review confirm the effectiveness of TQ in various pathologies viz. inflammation, cancer, diabetes, gastric, hepatic, microbial and allergies. However, the complete clinical benefit of TQ has not yet been realized, owing to its poor biopharmaceutical properties. Nevertheless, colloidal drug delivery carrier systems, could be impending in bringing forth this potential molecule to reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Thymoquinone (TQ, 2‐methyl‐5‐isopropyl‐1,4‐benzoquinone), a bioactive component extracted from the seeds of Nigella sativa , has been proved to exert wide‐ranging pharmacological activities, with anti‐tumor, anti‐inflammatory, anti‐oxidant, anti‐microbial, anti‐convulsant and anti‐diabetic properties . Therefore, TQ has been regarded as a promising agent for numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymoquinone (TQ, 2‐methyl‐5‐isopropyl‐1,4‐benzoquinone), a bioactive component extracted from the seeds of Nigella sativa , has been proved to exert wide‐ranging pharmacological activities, with anti‐tumor, anti‐inflammatory, anti‐oxidant, anti‐microbial, anti‐convulsant and anti‐diabetic properties . Therefore, TQ has been regarded as a promising agent for numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…has been proved to exert wide-ranging pharmacological activities, with anti-tumor, anti-inflammatory, anti-oxidant, anti-microbial, anti-convulsant and anti-diabetic properties. [6][7][8][9] Therefore, TQ has been regarded as a promising agent for numerous diseases. Previous studies have revealed that TQ may exhibit high anti-tumor efficiency against various cancers, such as breast cancer, gastric cancer, cervical cancer, colon cancer, central nervous system cancer, ovarian cancer, prostate cancer, bladder cancer and renal cell cancer.…”
mentioning
confidence: 99%
“…Prevention of the side effects of cisplatin is one of the major issues in treating cancer patients [9,10] and so various methods have been tested to prevent these side effects of cisplatin, such as combined use of free radical scavengers [6,7]. Therefore, the present study was designed to elucidate the availability of using some types of antioxidants of natural sources to alleviate these side effects upon cisplatin treatment [9,10]. In this study, TQ and Vit E were used either separately or in their combination form to declare their role in ameliorating the adverse effects of cisplatin induced nephropathy and hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone (the main constituent of Nigella sativa seed volatile oil) possesses strong antioxidant properties that protect against oxidative damage resulting from free radical-generating agents [8]. It was reported to have anti-inflammatory actions, an analgesic and a protective effect against chemical induced carcinogenesis [9,10]. Thymoquinone also have a protective effect against diabetic nephropathy [11].…”
Section: Introductionmentioning
confidence: 99%
“…TQ sebagai antioksidant dapat meningkatkan sekresi insulin dengan meningkatkan metabolisme energi di mitokondria dan meningkatkan jalur intraseluler pada reseptor insulin. Efek hipoglikemik pada TQ tidak hanya berkaitan dengan kerja insulin, tetapi juga kemampuan TQ untuk menurunkan glukoneogenesis dengan menekan sintesis enzim glukoneogenik (Negi, Rathore, Sharma, Singh, & Katare, 2018).…”
Section: Worldunclassified